ANALYSIS OF FINANCIAL STATEMENTS AS A TOOL FOR ASSESSING BANK PERFORMANCE USING PROFITABILITY RATIOS AT PT. BANK MUAMALAT INDONESIA TBK PERIOD 2017-2021 - Saifuddin Saifuddin; Suryana Dewi (Jurnal Ekonomi, 2023)
Bank Muamalat is the first pioneer of Islamic financial institutions whose business activities are based on the sharia system. The presence of Bank Muamalat in Indonesia is getting stronger after being able to get through the monetary crisis that occurred in Indonesia in 1997. But in the last few periods, PT Bank Muamalat Tbk has experienced problems in its financial system which resulted in developments in its financing system which resulted in a decline in its finances which led to a reduction in customer interest in Bank Muamalat. This study aims to describe the financial performance of Bank Muamalat in Indonesia which can be seen from the Profitability ratio which is submitted periodically in each period. This research is a field study research in the form of data documentation from the financial statements of PT Bank Muamalat Tbk for five years by describing the results of the company's financial performance to assess bank performance from the aspect of profitability ratios and then compared with the standard value of Bank Indonesia's assessment criteria. This can be seen based on the calculations of ROA, ROE, NPM from 2017-2021 which show a very unfavorable financial condition, this is because the value generated from the ratio calculation is below the standard value of Bank Indonesia's assessment criteria. The average ROA of 0.04%, ROE of 0.51%, and NPM of 63.50% do not meet Bank Indonesia's assessment standards. This shows that Bank Muamalat is not competent in managing capital and does not increase financing to obtain bank profits and minimize bank operational costs properly. Meanwhile, the average GPM over the five-year period was 29.43% indicating a very good financial condition. This shows that the higher the GPM value, the better the operational conditions of the bank itself.